2020
DOI: 10.1096/fj.202000051rrr
|View full text |Cite
|
Sign up to set email alerts
|

Virulent Pseudomonas aeruginosa infection converts antimicrobial amyloids into cytotoxic prions

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 89 publications
3
45
0
Order By: Relevance
“…In turn, the present study identified amyloidogenic sequences of the S1 protein from P. aeruginosa that can be used to create antimicrobial peptides capable of targeting antibiotic-resistant strains of this pathogen. Such antimicrobial peptides containing amyloidogenic regions and acting by the mechanism of directed coaggregation with the ribosomal S1 protein may be a promising variant of a new type of antibiotics directed against microorganisms that cause nosocomial and other types of infections [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the present study identified amyloidogenic sequences of the S1 protein from P. aeruginosa that can be used to create antimicrobial peptides capable of targeting antibiotic-resistant strains of this pathogen. Such antimicrobial peptides containing amyloidogenic regions and acting by the mechanism of directed coaggregation with the ribosomal S1 protein may be a promising variant of a new type of antibiotics directed against microorganisms that cause nosocomial and other types of infections [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…8), with cystatin C binding to lower molecular weight forms secreted from uninfected cells while being associated with higher molecular weight complexes released from PA103 infected cells. A potential explanation for this varied binding response is provided by our recent studies which demonstrated that infection regulates the type of amyloid secreted from PMVECs [39]. Infection by strains of P. aeruginosa that lack a functional type III secretion system or produce catalytically inactive effector exoenzymes leads to the release of noncytotoxic forms of Aβ whereas infection with strains that contain functional type III secretion system and active effector enzymes leads to the conversion of Aβ into cytotoxic forms.…”
Section: Discussionmentioning
confidence: 99%
“…A third possibility is that binding of cystatin C to Ab is an adaptive mechanism of the bacterial cells and assists them with avoiding the innate immune response of the cells. Recent data indicate that beta amyloid oligomers are anti-bacterial in nature [37][38][39]. During evolution, the bacteria may have developed a system where they target cystatin C and induce its dimerization so that it inhibits assembly of beta amyloid into an anti-bacterial species.…”
Section: Hbss Pa103mentioning
confidence: 99%
“…Curli is capable of cross-seeding Aβ fibrillation, and treatment of S. Typhimurium with Denantiomeric peptides, known to inhibit Aβ fibrillation, inhibits curli fibrillation and reduces biofilm formation (121). Infection of pulmonary microvascular endothelial cells with clinical P. aeruginosa, which produce the bacterial amyloid FapC, induces production of Aβ and tau, capable of prion-like propagation to naïve cells (145). Evidence from animal models will be required to determine whether bacterial amyloids are capable of directly seeding Aβ or tau aggregation in a manner relevant to neurodegeneration.…”
Section: Neurological Diseasesmentioning
confidence: 99%